KARAKTERISASI KIMIA DAN MORFOLOGI BIOKOKAS DARI BAGLOG JAMUR DENGAN PEREKAT LIMBAH LILIN MALAM BATIK MENGGUNAKAN FTIR DAN SEM - Hamim Mahfudhillah; Siti Azzahra Santika; Adeecha Cinta Islamiah (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
The global energy crisis caused by the depletion of fossil fuels and increasing greenhouse gas emissions has accelerated the development of biomass-based renewable energy such as biocoke. This study aims to analyze the chemical and morphological characteristics of biocoke derived from mushroom baglog with batik wax waste binder using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Samples were used are raw mushroom baglog (M50%) and pyrolyzed baglog biochar (P50%), each mixed with 50% batik wax waste. The pyrolysis process was carried out at 350-400 °C for 3 hours in an oxygen-limited reactor. FTIR analysis revealed that M50% biocoke contained strong aliphatic C–H and O–H hydroxyl groups, indicating high moisture (7.55%) and volatile matter (41.75%). In contrast, P50% biocoke exhibited intensified aromatic C=C peaks (1588 cm⁻¹) and reduced O–H bands (3616 cm⁻¹), reflecting higher carbonization with 46.76% fixed carbon and a heating value of 27.31 MJ/kg. SEM micrographs showed a distinct morphological difference: M50% had a fibrous and highly porous structure, while P50% displayed a compact, homogeneous surface with micro-pores (1–10 µm). The combination of pyrolysis and batik wax waste addition produced biocoke with improved combustion stability, higher thermal efficiency, and lower exhaust emissions. In conclusion, pyrolysis significantly enhances the energy quality and structural stability of biocoke, while batik wax waste acts as an effective thermoplastic binder, improving particle homogeneity and calorific performance.